DOI: 10.14264/uql.2016.222
|View full text |Cite
|
Sign up to set email alerts
|

Shifting cultivation in the upland secondary forests of the Philippines: biodiversity and carbon stock assessment, and ecosystem services trade-offs in land-use decisions

Abstract: Secondary forest comprises a large area in the tropical region, and it has increasingly believed that the future of tropical forests depends on the effective management of such second growth forests largely modified by human activity. In tropical secondary forests, shifting cultivation, swidden or slash-and-burn is a major land-use that has been attributed to causing large scale deforestation and forest degradation. This view has been embedded in many policy documents, although there are conflicting views with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 110 publications
(194 reference statements)
0
6
0
Order By: Relevance
“…Regarding the impacts on the regeneration of fallows, the Kawaiwete and Ikpeng local knowledge seems to value preventive care during cultivation phases aiming to prevent the forest from being degraded, instead of resorting to concepts or ways of restoring exhausted environments. In this sense, traditional local knowledge seems to indicate rules or "care" in the way environments should be managed based on resilience limits, as observed for other places (Lugo, 1995;Camacho et al, 2012;Chazdon, 2014a;Magnuszewski et al, 2015;Chazdon and Guariguata, 2016;Brancalion et al, 2016;Mukul, 2016;Vásquez-Grandón et al, 2018).…”
Section: Traditional Kawaiwete and Ikpeng Forest Management Practicesmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the impacts on the regeneration of fallows, the Kawaiwete and Ikpeng local knowledge seems to value preventive care during cultivation phases aiming to prevent the forest from being degraded, instead of resorting to concepts or ways of restoring exhausted environments. In this sense, traditional local knowledge seems to indicate rules or "care" in the way environments should be managed based on resilience limits, as observed for other places (Lugo, 1995;Camacho et al, 2012;Chazdon, 2014a;Magnuszewski et al, 2015;Chazdon and Guariguata, 2016;Brancalion et al, 2016;Mukul, 2016;Vásquez-Grandón et al, 2018).…”
Section: Traditional Kawaiwete and Ikpeng Forest Management Practicesmentioning
confidence: 97%
“…Forest and agricultural management often leads to changes in species composition and in soils (Smith, 1980;Balée, 1993;Heckenberger and Neves, 2009;Arroyo-Kalin, 2010;Junqueira et al, 2011;Woods et al, 2013;Schmidt et al, 2014;Levis et al, 2018Levis et al, , 2020, and are based on a deep knowledge of ecological dynamics and on social and cultural rules (Berkes and Berkes, 2009). The shifting cultivation practiced by indigenous Amazonian peoples depends on the multifunctional management of the landscape during the cultivation phase (van Vliet et al, 2012;Mukul, 2016), which includes the simultaneous cultivation of several cultivated/domesticated and semi-domesticated species (Hett et al, 2012). The combination of social and ecological dynamics leads to different successional trajectories (Wangpakapattanawong et al, 2010;Chazdon, 2014b;Chazdon and Uriarte, 2016;Uriarte and Chazdon, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In each of our study sites we identified tree species that were at least 5 cm at dbh (diameter at breast height) and measured diameter and height. More about our survey design and data collection can be found at Mukul (2016).…”
Section: Ecological Surveysmentioning
confidence: 99%
“…Shifting cultivation, locally termed as kaingin is a widespread land-use in the Philippines (Kummer 1992). It is also a major livelihood strategy to many smallholder farmers living in the remote rural areas of the country (Mukul 2016;Herbohn et al 2014). However, alike many other tropical countries, major forestry policies in the Philippines have attempted to impose restrictions on kaingin, based on the assumption that it has detrimental impacts on the environment (Saurez and Sajise 2010; Lawrence 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Short fallows trigger yield declines (Kafle 2011). After shifting cultivation both the fallow age and land use intensity influence the recovery of native trees diversity (Mukul 2015); the forest degradation and subsequent rural poverty worsens in a cycle when there are few economic alternatives, unstable or low market prices, no incentives for innovation, and successive subdivision of land at the death of the owner (Chayanov 1966) (figure 1).…”
Section: Introductionmentioning
confidence: 99%